Sensory-Cognitive Interior Design Model for Improved Learning Outcomes in Art and Design Institutions - Kaleem, Samia (Journal of Design and Textiles, 2022)
The current research is a critique on the education community that follows a single standard of design and space. Moreover, it is expected to cater all forms of study from the primary to the higher education sectors. This statement stands true for a design school as well. Whereas, the indoor built environment contains the ability to affect and unfolds the mind of the students and also provides social opportunities, which in turn, influence the ability of the learners to think from different perspectives. This study mainly strives to enable the learners to interact with the world around them and to grow their learning capacities rather than being limited to their desks. Furthermore, it also allows them to be able to speak freely without any mental constrains and fears that are usually uphold by the traditional classical settings of the classroom. Eventually, the understanding of these connections becomes the basis of the ‘Design Center’ that aims to use the interior design elements to create a chance of new meetings rooms. Hence, allowing it to become a stimulant for an active learning space. Index Terms: Active learning space, Cognition, Design Studio, Interior design, Spatial behavior.